Jatimalang Beach Tourism Management Strategy, Purworejo District - Vicki Dwi Purnomo (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
The focus of this research is the strategy and development of beach tourism in Purworejo Regency in managing Jatimalang beach tourism objects. The purpose of this study was to determine the strategy of the Purworejo district government in managing the Jatimalang beach tourism object. The method used in this study is qualitative with a descriptive approach using conceptual models of theories related to management and development strategies according to Karyono (1997). The results of the study show that the strategy of the Purworejo Regency Government service in managing the Jatimalang beach tourism object has not been maximized because many of the strategies made are still at the planning stage. The supporting factors in managing the Jatimalang beach are investors who want to work together and the potential for a good beach and the inhibiting factors are unclear land ownership status, budget constraints, and lack of public awareness in caring for Jatimalang beach facilities and infrastructure.